Characteristics and Growth Rate of Lung Metastases in Patients With Primary Gastrointestinal Malignancies and Lung-dominant Metastatic Disease: A Retrospective Cohort Analysis. (6th December 2021) - Burns, Shohei; Vella, Maya; Paciorek, Alan; Zhang, Li; Atreya, Chloe E.; Feng, Mary; Kelley, Robin K.; Tempero, Margaret A.; Van Loon, Katherine; Ko, Andrew H.
Abstract : Introduction: There are no formal guidelines for the management of patients with primary gastrointestinal (GI) cancers who have lung-exclusive or lung-predominant metastases. We performed a retrospective analysis to evaluate host and tumor characteristics of this patient population, model patterns and rates of growth, and describe treatment approaches. Materials and Methods: Eligible patients had a GI cancer with either synchronous or metachronous lung metastases but no other visceral or peritoneal sites of involvement. In addition to collecting detailed patient-specific and tumor-specific information, all imaging studies (computed tomography±positron emission tomography scans) were reviewed by an independent radiologist. Up to 5 lung metastases were tracked through each patient's clinical course. Growth rate was estimated using a linear mixed model analysis. Results: Forty patients met eligibility criteria (18 pancreatic, 15 colorectal, 6 hepatobiliary, 1 gastroesophageal; synchronous vs. metachronous, 13 and 27, respectively). Median time from original cancer diagnosis to onset of metachronous lung lesions was 16 months. Interval from first appearance of lung metastases to treatment initiation was 6.2 months. Average growth rate of the largest lesion was 0.21 mm/mo (95% confidence interval, 0.12-0.30), with substantial intrapatient and interpatient variability. Sixty percent of patients underwent locoregional interventions in addition to or in lieu of systemic therapy for their lung metastases. Median survival of the entire study cohort from first appearance of lung metastases was 54 months. Conclusions: Lung metastases from primary GI cancers have a variable but overall indolent natural history and are generally associated with prolonged survival outcomes. Further efforts to define patterns of growth of lung metastases, informed by size, number, and clinical/molecular features, are needed to guide appropriate timing and selection of therapy as well as surveillance strategies.